Answer:
Just took the quiz ;-; the answer is "0.512"
Thank me later xD
help please....
A. 0.354.
B. 3.54.
C. 354.
D. 35.0
J
‾
HJ
. Given
I
J
=
3
x
+
3
,
IJ=3x+3,
H
I
=
3
x
−
1
,
HI=3x−1, and
H
J
=
3
x
+
8
,
HJ=3x+8, determine the numerical length of
H
J
‾
.
HJ
.
Answer:
Step-by-step explanation:
the answer is 14
For any value of x, h(x) will always be greater than g(x).
g(x) > h(x) for x = -1.
g(x) < h(x) for x = 3.
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).
Answer: g(x) > h(x) for x = -1.
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).
Step-by-step explanation:
Given functions: and
When x=0, and
∴ at x=0, g(x)=h(0)
Therefore the statements "For any value of x, g(x) will always be greater than h(x)." and "For any value of x, h(x) will always be greater than g(x)." are not true.
When x=-1, and
∴g(x) > h(x) for x = -1. ......................(1)
When x=3, and
∴ g(x) > h(x) for x = 3....................(2)
⇒g(x) < h(x) for x = 3. is not true.
From (1) and (2),
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).
Answer:
y = 65 when x = 13
Step-by-step explanation:
Here we have a proportion problem.
Y varies directly as x means that y equals the product of x and a constant
Let’s say our constant is k
Thus;
y = kx
now, k = y/x
Using the initial values;
k = 25/5 = 5
Now we want to get y when x = 13
Recall; y = kx
Thus using the value of k earlier calculated;
y = 13 * 5
y = 65